Frontiers of vascular biology and disease research - Chen Alex F; Tang Chao-shu (Acta Pharmacologica Sinica, 2016)
2010 represents a special year for Acta Pharmacologica Sinica, the 30th anniversary of its debut as an international journal. On this memorable occasion, the journal and its guest editors are proud to present to our readers a special issue in vascular biology and disease research. The research work presented herewith spans from molecular cardiovascular biology to integrated physiology and pharmacology.